ACCEPTANCE OF SELF-EVALUATION OF TEACHERS IN LOWER PRIMARY SCHOOLS - Esad Kurejšepi (Human Research in Rehabilitation, 2013)
Acceptance of self-evaluation as a complex, challenging activities and competencies of teachers ceased to be the issue of his personal choice, so this process the teacher must accept as an unavoidable factor in their professional development and, in the classroom, to take responsibility for the affirmation of pedagogy and design appropriate learning environment for it.